Operationalizing Living Law to Ensure Fair Trial and Prevent Abuse of Power in Indonesia’s Criminal Justice System - Hana Krisnamurti; Dewi Asri Yustia; Sri Mulyati Chalil (Universitas Islam Sultan Agung, 2026)
This study analyzes the role of living law in realizing the principle of fair trial within the Indonesian criminal justice system following its formal recognition in the Indonesia’s 2023 Criminal Code. It aims to examine how living law can be operationalized as a legal instrument to bridge the gap between formal legality and substantive justice, while preventing abuse of power across criminal proceedings. Despite its normative acknowledgment, the implementation of living law remains inconsistent and often constrained by a positivistic legal approach, resulting in disparities and legal uncertainty in judicial practice. This research employs a normative juridical method using statutory and conceptual approaches, supported by an analytical-descriptive design based on secondary legal materials, including legislation, jurisprudence, and legal doctrines. The findings demonstrate that living law contributes significantly to the realization of fair trial principles by incorporating societal values, ensuring proportionality in sentencing, recognizing customary sanctions, and preventing double punishment (ne bis in idem). However, the absence of standardized criteria, formal validation mechanisms, and procedural guidelines creates risks of subjectivity and arbitrariness. The novelty of this study lies in positioning living law as an operational and structured legal mechanism within criminal justice, emphasizing the need for a comprehensive regulatory framework integrated with human rights safeguards to ensure legal certainty, consistency, and substantive justice.